ANALISIS EFEKTIVITAS POMPA PASARWARU SISTEM DRAINASE TENGGANG - Fitria Maya Lestari; Burhanudin Mukhamad Noor; Puja Aulia; Moch Sediono (Teknika, 2026)
The Pasar Waru area in Semarang City is one of the flood-prone regions, influenced by high rainfall intensity, land subsidence, and a suboptimal drainage system. The drainage system in this area consists of four main channels leading to the Pasar Waru Pump Station, which serves as the final control point before water is discharged into the main outlet, the East Flood Canal. This study aims to analyze the effectiveness of the drainage system and pump station in conveying surface runoff from the study area using hydrological and hydraulic analysis. Based on hydrological analysis, runoff discharge was calculated using the Rational and Hasper methods. Channel 4, with a 10-year return period, produces a discharge of 13.30 m³/s, while the existing channel capacity is only 11.14 m³/s, indicating overflow. Thus, an increase in capacity to 13.45 m³/s is required to accommodate the runoff. Other channels already meet the design discharge capacity, including Channel 1, which has been upgraded to 9.24 m³/s. In terms of storage, Retention Pond 1 with a capacity of 85,669.2 m³ can store 19.41 m³/s of discharge for 60 minutes. However, Retention Pond 2, with a volume of 22,187.2 m³, is insufficient to store 20.17 m³/s for 20 minutes, indicating the need for dimensional enlargement to increase its capacity. The existing pump station system includes two pump units with a total capacity of 63.474 m³/s and is capable of handling a runoff discharge of 23.889 m³/s after considering the flood discharge of 39.585 m³/s. Overall, the existing drainage system and pump station in the Pasar Waru area are considered fairly effective in supporting flood control, although further optimization of channels and enhancement of retention pond capacity are necessary to reduce inundation risk.